PERSEPSI SISTEM PENGUPAHAN DALAM KAITANNYA DENGAN KOMITMEN ORGANISASI - Rosita Endang Kusmaryani (LPPM UNY, 2004)
Abstract This study aimed to find the positive correlation of perception of pay system with organizational commitment. Especially it aimed to know: 1) the positive correlation of each perception of pay system aspects with organizational commitment; 2) the positive correlation of perception of pay system with three organizational commitment aspects (affective, continuance, normative). This study involved 95 employees of PT Kusuma Sandang Mekarjaya Yogyakarta as respondents. Data were collected by using two scales to employees; those were perception of pay system scale and organizational commitment scale. Based on regression analysis found:1) there was a very significantly positive correlation of perception of pay system with organizational commitment; 2) there were very significantly positive correlations of each perception of pay system aspects with organizational commitment, and 3)there were very significantly positive correlation of perception of pay system with three organizational commitment aspects (affective commitment, continuance commitment, and normative commitment) Keywords: perception of pay system, organizational commitment (affective, continuance, normative)